The Influence of Lifestyle and Perceived Ease of Use of Shopee PayLater on Consumer Purchase Decisions - Rhika Sindi Amelia; Ahmad Johan; Taufik Sadikin (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of lifestyle and perceived ease of use of Shopee PayLater on consumer purchase decisions. A quantitative approach with descriptive and verificative methods was employed in this research. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling techniques. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing with SPSS software. The findings reveal that lifestyle has a positive and significant effect on purchase decisions. Furthermore, the perceived ease of use of Shopee PayLater demonstrates a stronger positive and significant influence on purchase decisions. Simultaneously, both variables significantly affect purchase decisions and contribute substantially to explaining consumer purchasing behavior. The study implies that digital payment providers and e-commerce platforms should enhance user-friendly payment features and align their marketing strategies with consumers’ lifestyle trends to encourage purchasing decisions. These findings also contribute to the development of consumer behavior and financial technology research in the digital commerce context.